Utilizing Energy Efficiency and QoS awareness for Receiver-Arbitrated and Sender-Predicted MAC Protocol in Wireless Sensor Network. Issue 1 (February 2021) - Yang, Huan; Bao, Lingyan; Luo, Jia; Deng, Biao; Wang, Hui
Abstract: In this paper, we exploit energy-efficiency and QoS-awareness for receiver-arbitrated and sender-predicted MAC Protocol (EQAP-MAC) in wireless sensor network. EQAP-MAC improves the transmission concurrency by separating control stream from data stream; minimizes energy consumption by sender by predicting receiver's wake-up time; supports priority-based QoS through priority-based data flow selected, arbitrated and interrupted mechanisms; reduces transmission interference between the nodes by interleaving neighbor nodes' wake-up time; improves system throughput and reduces the data stream transmitting delay by pipelining mechanism and optimizing send sequence. We have implemented EQAP-MAC on TinyOS and evaluated its performance on testbed. The result shows EQAP-MAC achieves higher concurrent performance and priority-based QoS guarantee with lower energy consumption compared with RI-MAC and X-AMC.